2015
DOI: 10.1021/acsnano.5b01677
|View full text |Cite
|
Sign up to set email alerts
|

Freestanding van der Waals Heterostructures of Graphene and Transition Metal Dichalcogenides

Abstract: Vertical stacking of two-dimensional (2D) crystals has recently attracted substantial interest due to unique properties and potential applications they can introduce. However, little is known about their microstructure because fabrication of the 2D heterostructures on a rigid substrate limits one's ability to directly study their atomic and chemical structures using electron microscopy. This study demonstrates a unique approach to create atomically thin freestanding van der Waals heterostructures-WSe2/graphene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
142
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(151 citation statements)
references
References 46 publications
9
142
0
Order By: Relevance
“…Possible candidates for further studies are few layer graphene sheets, single layer hexagonal boron nitride/graphene compounds, exfoliated single layer molybdenum disulphide [31], or heterostructures of graphene and transitional metal dichalcogenides [32].…”
Section: Discussionmentioning
confidence: 99%
“…Possible candidates for further studies are few layer graphene sheets, single layer hexagonal boron nitride/graphene compounds, exfoliated single layer molybdenum disulphide [31], or heterostructures of graphene and transitional metal dichalcogenides [32].…”
Section: Discussionmentioning
confidence: 99%
“…The next best candidates are two-dimensional transition-metal dichalcogenides (TMDCs) which are direct band-gap semiconductors [16,17]. Graphene on TMDCs has already been grown [18][19][20] and investigated for transport [21,22] as well as considered for technological applications [23][24][25][26]. It was recently predicted that monolayer MoS 2 will induce a giant spin-orbit coupling in graphene, of about 1 meV (compared to 10 ÎŒeV in pristine graphene [27]).…”
Section: Introductionmentioning
confidence: 99%
“…[60] Subsequently, Alem et al, reported the syntheses of nearly freestanding MX 2 /Gr heterostructures on Quantifoil TEM grids with ≈2 ÎŒm holes by the APCVD growth of monolayer MX 2 on transferred monolayer Gr (from Cu foils) (Figure 8c). [127] Notably, this work enabled the on-site investigation of the growth dynamics of MX 2 on Gr surfaces at an atomic resolution. [51] Copyright 2015, American Chemical Society.…”
Section: Cvd Syntheses Of MX 2 /Gr Heterostructuresmentioning
confidence: 99%